ODESSA SCIENTIFIC SCHOOL OF RESEARCHERS OF VARIABLE STARS: FROM V.P.TSESEVICH (1907-1983) TO OUR DAYS - Andronov, I. L. (Одеські астрономічні публікації, 2017)
The biography of Vladimir Platonovich Tsesevich (11.11.1907 – 28.10.1983), a leader of the astronomy in Odessa from 1944 to 1983, is briefly reviewed, as well as the directions of study, mainly the highlights of the research of variable stars carried out by the members of the scientific school founded by him. The directions of these studies cover a very wide range of variability types – “magnetic” and “non-magnetic” cataclysmic variables,symbiotic, X-Ray and other interacting binaries, classical eclipsers and “extreme direct impactors”, pulsating variables from DSct and RR through C and RV to SR and M.Improved algorithms and programs have been elaborated for statistically optimal phenomenological and physical modeling. Initially these studies in Odessa were inspired by ("with a capital letter") Vladimir Platonovich Tsesevich. who was a meticulous Scientist and brilliant Educator, thorough Author and the intelligibly explaining Popularizer,persevering Organizer and cheerful Joker – a true Professor and Teacher. He was “the Poet of the Starry Heavens”.